(3GdJQJjH HCbd eG jMaXg GdCOjHs - (3GdcjhGfj , CMeO Hf MSjf HGTG Hf eUWaj Hf MSjf Hf eMeO Hf cjhGf, GdcjhGfj,J (B1173 (3g` s
(3ChdgG (B:s
(3hYdi GdEfSGf eGde jYde CcQeg HGdYbd hGdEjeGf hGdYde hGdMceI hGdHjGf s
(3BNQgG (B:s
(3fQLhG HCf jfaYfG HgG hef jJHYgG JeJ GdCQLhRI GdeSeGI HCbd eG jMaXg GdCOjH s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3fXe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B108s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs